Do women's sociodemographic characteristics or type of prenatal care provider influence quality of prenatal care? - Kandasamy, Mayura (My University, 2013)
Do women’s sociodemographic characteristics or type of prenatal care provider influence quality of prenatal care?
Objective: This study examined whether sociodemographic characteristics or type of prenatal care provider influenced the quality of prenatal care received by women in Canada. The main predictors of high quality prenatal care received by Canadian women were identified.
Methods: A secondary analysis of data collected for a primary study that developed and tested the Quality of Prenatal Care Questionnaire (QPCQ) was conducted. Women (n=422), recruited from five cities, completed a background questionnaire and the QPCQ. Data analysis involved examining nine sociodemographic variables and one prenatal care provider variable using independent samples t‐ tests, one‐way analysis of variance, and analysis of covariance.
Results: Statistically significant differences in prenatal care quality were noted among women based on language spoken at home, racial background, marital status, family income, and education level. Women receiving midwifery care reported the highest quality of prenatal care, compared to women receiving care from obstetricians who reported lower quality prenatal care. The strongest predictors of high quality prenatal care were type of prenatal care provider and total family income.
Conclusions: Efforts to universally improve quality of prenatal care in Canada require practice, policy, and research initiatives. Incorporating alternative/ancillary prenatal care services has the potential to improve access, psychosocial supports, appropriate referrals, education, and interventions for women receiving lower quality prenatal care. Systemic practice and policy changes to increase midwifery care capacity would enable midwives to provide high quality prenatal care to a larger portion of low risk Canadian women. Shared care models could reduce the burden on obstetricians, enabling them to provide higher quality prenatal care to high risk Canadian women. Future research needs to focus on identifying the efficacy of each prenatal care component and examining their specific effects on birth outcomes.
Keywords: prenatal care; quality of prenatal care; sociodemographic characteristics; type of prenatal care provider; predictors; Quality of Prenatal Care Questionnaire (QPCQ); Maternal, Child Health and Neonatal Nursing; Maternal, Child Health and Neonatal Nursing